2016
DOI: 10.1016/s1514-0326(16)30013-7
|View full text |Cite
|
Sign up to set email alerts
|

Banking Instability and Deposit Insurance: The Role of Moral Hazard

Abstract: This paper aims at empirically investigating the role of moral hazard in the e¢ ctivity of deposit insurance in achieving banking stability. If the negative e¤ect of deposit insurance on banking stability is through moral hazard, then deposit insurance will be associated with banking insolvency and credit crunch more than with bank runs. To test this hypothesis, we compute measures of these two types of banking instability. We …nd that deposit insurance per se has no signi…cant e¤ect either on bank insolvency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 33 publications
0
12
0
4
Order By: Relevance
“…Using a sample of developing and developed countries between 1980 and 1994, one study found that a deposit insurance scheme is negatively correlated with bank stability (Demirgüç-Kunt and Detragiache 2002). Another study that uses cross-country panel data between 1980 and 2004 also finds an effect of a deposit insurance scheme on bank insolvency and bank runs (Ngalawa et al 2016). A similar study also shows that the implementation of a deposit insurance scheme increases the likelihood of bank failure (Hooks and Robinson 2002), loan-deposit rate spread (Carapella and Giorgio 2004), and moral hazard (Yilmaz and Muslumov 2008).…”
Section: Introductionmentioning
confidence: 78%
“…Using a sample of developing and developed countries between 1980 and 1994, one study found that a deposit insurance scheme is negatively correlated with bank stability (Demirgüç-Kunt and Detragiache 2002). Another study that uses cross-country panel data between 1980 and 2004 also finds an effect of a deposit insurance scheme on bank insolvency and bank runs (Ngalawa et al 2016). A similar study also shows that the implementation of a deposit insurance scheme increases the likelihood of bank failure (Hooks and Robinson 2002), loan-deposit rate spread (Carapella and Giorgio 2004), and moral hazard (Yilmaz and Muslumov 2008).…”
Section: Introductionmentioning
confidence: 78%
“…Dummy variable "government ownership" takes the value 1 if the share of state ownership is higher than 50% and the opposite value = 0. It addresses the hypothetical incentives for the shareholders to assume higher risks if the potential governmental support is available (Cheng et al, 2016;Mariathasan et al, 2014;Ngalawa et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…They suggest that the governmental guarantees reduce the downside risk associated with financing decisions and thus incentivize the banks to assume risks they would not choose to bear without the expected government support. Duran and Lozano-Vivas (2012), Ngalawa et al (2016) indicate further that generous deposit insurance schemes seem to incentivize risk shifting to the non-depository creditors. By comparing the different forms of the government support, Janda (2011) concludes that in some situations the credit guarantees and interest rate subsidies are beneficial for borrowers and lenders, e.g.…”
Section: Introductionmentioning
confidence: 98%
“…S druge strane, mnoga istraživanja (npr. Cull et al, 2002;Davis, Obasi, 2009;Lé, 2013;Ngalawa, 2016) dokazala su kako eksplicitni sustavi mogu stvoriti negativne efekte poput nestabilnosti bankovnog sustava i/ili kriza te povećanja moralnog hazarda banaka. Ipak, empirijski dokazi o povezanosti eksplicitnog sustava osiguranja depozita i povećanog preuzimanja rizika su nekonzistentni jer učinak ovisi i o vlasničkoj strukturi sustava osiguranja depozita kao i drugim institucionalnim karakteristikama.…”
Section: Pregled Literatureunclassified